2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Immigration Reform Programs [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
A national policy on immigration is established which requires that all employers hire only those persons legally entitled to work in the United States. This is EDIS document FE402, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.